2020 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) 2020
DOI: 10.1109/i2mtc43012.2020.9128465
|View full text |Cite
|
Sign up to set email alerts
|

Online Quality Assurance of Microchannels in Roll-to-Roll by Optical Coherence Tomography

Abstract: Roll-to-roll (R2R) process is an emerging technology to manufacture printed electronics, microfluidics, biochemical sensors etc. The requirements for high quality and small tolerances at the manufacturing phase are of the essence for such products. To verify the quality and guarantee the high production yield, high speed, non-destructive testing methods are needed. In this paper, optical coherence tomography (OCT) device is used at the R2R-line to measure online hot embossed microchannel structures at speed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The WSI processing algorithm was applied to determine surface position at nanometer-scale resolution. This improved the resolution compared to the method based on only the maximum intensity [22], of which resolution was, without zero padding, 2.7 µm (2.7 mm/1024). The heights and widths were automatically determined for two different hot embossing pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WSI processing algorithm was applied to determine surface position at nanometer-scale resolution. This improved the resolution compared to the method based on only the maximum intensity [22], of which resolution was, without zero padding, 2.7 µm (2.7 mm/1024). The heights and widths were automatically determined for two different hot embossing pressures.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently applied OCT for surface topography measurements at the R2R-line [22], however, in those measurement OCT suffered from the poor depth resolution due to the lack of WSI capability, and therefore, heights of the channels were not determined. In this study, we use a WSI algorithm to obtain surface topography at nanometerscale resolution without losing micrometer resolution tomography information.…”
Section: Introductionmentioning
confidence: 99%
“…Optical Coherence Tomography (2.10) Thickness, Internal topography, refractive index [34] Polymers, semitransparent films, biological samples 1 m min −1 (not including data processing) [34] 1D OCT: frame rate of 97.66 fps; 3D OCT prototype: frame rate of 30.6 fps. [35] Vertical resolution: 5.8 microns; Lateral resolution: 91 microns @ web speed of 1 m min Has significant potential for R2R applications as it can be used in reflection and transmission mode [36] and complete probe/sensor can be integrated into a compact fiber package.…”
Section: Areal Thickness Displacement Surface Topographymentioning
confidence: 99%
“…Lauri, J. et al (2019) demonstrated OCT for inline R2R monitoring of the structure of hot-embossed microchannel in PMMA webs. [34] For static offline measurement, the commercial Thorlabs OCT system used is capable of vertical (depth) resolution of 5.8 µm (in air) and lateral resolution of 8 µm. For inline measurement, the effective lateral resolution in the longitudinal direction was 91 µm.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Because the channel is open to the atmosphere, nanoparticles can be deposited in microchannels by evaporating a colloidal suspension. This strategy has been applied to the fabrication of printed electronic devices, such as conductors, resistors, and low-pass filters, where open rectangular microchannels were used due to their ease of fabrication. Printed electronic devices are of considerable technological importance because they are low-cost, flexible, and light. Additionally, open rectangular microchannels appear in microfluidic devices for applications, such as heat pipes , and artificial lungs .…”
Section: Introductionmentioning
confidence: 99%